1836 Tenn. Comp. Stat. 496, Misdemeanors, 1835-Chapter 58, § 2 - (:unkn) unknown (My University, 1835)
Prohibited any "free person" from selling, loaning, or giving any gun, pistol, sword, or dirk to "any slave."
Keywords: ENSLAVED PERSONS & OTHER MINORITIES